Valuing the caregiver: a feasibility study of an acceptance and commitment therapy (ACT) group intervention for dementia caregivers. Issue 1 (8th December 2020) - George, Catriona; Boyce, Mandy; Evans, Rosalind; Ferreira, Nuno
Abstract : Purpose: This study aims to investigate the feasibility and acceptability of a new group intervention, using an acceptance and commitment therapy (ACT) approach, developed for dementia caregivers. Preliminary data regarding the effectiveness of the intervention was also collected. Design/methodology/approach: A quasi-experimental design is used involving pre- and post-intervention data from four different intervention sites, along with three-month follow-up data. Data on attendance, attrition and qualitative feedback was also collected as an indication of acceptability. A total of 23 people currently caring for a family member with dementia attended the ACT group intervention for five sessions. Detailed evaluation forms were collected at the end of each group, along with four self-report questionnaires: Zarit Burden Interview, Positive Aspects of Caregiving Scale, Dementia Management Strategies Scale and Experiential Avoidance in Caregiving Questionnaire. Findings: Findings indicate that the group intervention was feasible and acceptable to caregivers, with subjective change reported in understanding of behavioural changes in the care-recipient, ability to handle negative emotions and valued living. These changes were not reflected in the outcome measures, with only one change reaching statistical significance (reduction in "intolerance of negative thoughts and emotions towards the relative"). Suggestions are made regarding possible alternative outcome measures for future studies to capture participants' experience more fully, along with potential adaptations and future directions for the intervention. Originality/value: This study provides preliminary evidence of the acceptability and feasibility of a group therapeutic intervention based on ACT for informal caregivers of dementia.